KARAKTERISTIK HABITAT LUTUNG BUDENG (Trachypithecus auratus) DI HUTAN LINDUNG PETUNGKRIYONO PEKALONGAN, JAWA TENGAH - , ARDYAN SYAFII; , Dr. Muhammad Ali Imron, S.Hut, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Javan langur is an endangered primate species and endemic in Java, which is the highest density populated island in the world. To conserve this protected species under dominated human landscape, understanding habitat characteristics is an important step for conceiving their adaptation ability. The objectives of this study is knowing characteristic of habitats that are used by javan langur, knowing the difference characteristic between habitat used and habitat unused, and also to know the distribution of javan langur habitat in Petungkriyono protected forest. Javan langur population in Petungkriyono protected forest under management of PT. PERHUTANI, in Central Java was choosen for this study. Sample were divided into used plots and unused plots were placed in the study location with search sampling technique. Important value index, Shannon-Wiener diversity index and sorensen comunity similarity index were calculated. Kruskal Wallis test was used to identify the difference between variable in used and unused habitats. Binary logistic regression test was carried out to investigate habitat selection model. Twenty plots were used and thirty six were unused by javan langur during study periods in August 2013. Habitat characteristics of the langur were describe as the following variables: temperatures range between 20-25oC, humidity is above 50%, medium slope, high vegetation diversity, crown cover is 86,24%, the number of tree ranges between 150-400 individuals/hectare and average number of feeding tree is 120 individuals/hectare. Crown cover, trees cover, number of seedling, pole, trees and feeding trees are significantly different between used and unused habitat. The presence of javan langur in Petungkriyono is determined by crown cover and number of feeding tree. Value of determination regression coefficient logistics is 64,6 % with level of accuracy exactness the presence or absence of javan langur is 89,3 %.